Hubungan Learning Contract dengan Kedisiplinan Siswa dalam Pembelajaran Pendidikan Jasmani Kelas 8 SMP Negeri 1 Purwasari: Using contract learning methods for student discipline - Cut Irawati; Resty Gustiawati; Ruslan Abdul Gani (Jurnal Literasi Olahraga, 2020)
This study aimed to determine the relationship between learning contracts with students’ discipline in Physical Education learning at class VIII of SMP Negeri 1 Purwasari. The background of this problem was the lack of students discipline in physical education learning so that the author tried to use a learning contract to see how students’ discipline in Physical Education learning. This research method was correlational. The population of this study was all the students at class VIII of SMP Negeri 1 Purwasari, with a sample number of 102 students. The data collection techniques used were observation and questionnaire. The data analyses used were descriptive data analysis techniques and inferential analysis techniques (by using Pearson product-moment correlation analysis techniques). The results of this study indicated that the r count was greater than r table then it can be concluded that there was a significant positive correlation between learning contracts with student discipline showing a positive correlation of 37.45%. With the t distribution table, with a significant level of 0.05 and dk = 102 so that the r table = 0.195 was obtained. Because r count was greater than the r table (0.612> 0.195).